(untitled) (Universal International Scientific Journal, 2026)
This article discusses age-related morphological and functional changes in human blood vessels, their causes, and their physiological and clinical significance. The study analyzed changes in arteries, veins, and capillaries, such as endothelial dysfunction, a decrease in elastic fibers, an increase in collagen, arterial stiffness, and a decrease in venous tone. With age, blood vessels lose their elasticity and blood pressure increases, which increases the load on the cardiovascular system. The article also discusses in detail oxidative stress, a weakening of the antioxidant system, disorders in neurohumoral control, and processes of atherosclerosis. This article is a review of the literature on gerontology, physiology, and clinical medicine.